Wetlands Construídos: economia, ecologia e sustentabilidade - Medeiros, Elisa Pereira (2023)
This study aims to infer how the Constructed Wetlands (CW) system can contribute to achieve universal access to sanitary sewage in Brazil. CW are a wastewater treatment alternative that simulates a swamp-like ecosystem by using biological processes, with plants and microorganisms. Therefore, an investigation will be conducted in the literature about the dynamics of CW systems and their relationship with the guiding assumptions of Neoclassical Environmental Economics and Ecological Economics. Among the results discussed is the fact that the system is not always the less expensive alternative, especially in consideration of expenses with earthmoving works. Technology is related to the assumptions of Environmental Economics in its two strands, Natural Resources Economics and Economics of Pollution. However, the economic and social characteristics of the sanitation sector do not coincide with the fundamentals that support the neoclassical theory. As for Ecological Economics, the solution equates with the fundamentals of theory, even though it requires monitoring the treatment process and the ecosystem. The conclusion is that in order to achieve the goals of sanitation sewage universalization, it is necessary to expand public policies to encourage the use of Constructed Wetlands and other decentralized systems in Brazil, mainly in rural areas and isolated regions from urban centers.